PENGARUH MODEL PEMBELAJARAN EXPERIENTIAL LEARNING TERHADAP KEMAMPUAN MENULIS TEKS CERPEN SISWA - Viona Shaka Ramdhanti; Silvia Marni; Iswadi Bahardur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the effect of applying the Experiential Learning model on the short story writing skills of students in phase F at SMA Negeri 12 Padang. The background of this study is based on the low interest and skills of students in writing short stories, especially in finding ideas and themes. The method used is an experiment with a One Group Pretest-Posttest Design. The research sample consisted of 34 students in phase F at SMA Negeri 12 Padang, selected using purposive sampling. The research instrument consisted of a short story writing performance test before (pretest) and after (posttest) the implementation of the Experiential Learning model. The results of the study showed a significant improvement in short story writing skills after the implementation of the Experiential Learning model, with significance (Sig.2-tailed) < 0.05, meaning that H0 was rejected and H1 was accepted. The average pretest score was 42.16, categorized as “poor,” while the average posttest score improved to the “good” category. Therefore, it can be concluded that the Experiential Learning model significantly influences the improvement in short story writing skills of Phase F students at SMA Negeri 12 Padang.